The Translation of Animal Metaphors in Politics between English and Arabic - Almaani , Bashar (Dirasat: Human and Social Sciences, 2023)
Objectives: This study aims to examine the conceptualization of animal metaphors in political speeches delivered by Abdullah II, the King of Jordan, and President Trump. Additionally, the research investigates the translatability of metaphors between English and Arabic in political speeches. Methods: The study analyzes metaphors using the conceptual theory of metaphor. Translated metaphors are examined based on the triangulation of translation procedures suggested by Schäffner (2004) and Deignan et al. (1997). Results: The study reveals that metaphors play a significant role in shaping political discourse and serve as influential devices used by politicians to persuade their audience and communicate complex political ideas, particularly in relation to topics such as terrorism. Regarding the translatability of metaphors, the study finds that the similarities outweigh the differences, primarily in terms of the correspondence in the number of conceptual domains. Conclusions: It is widely acknowledged that metaphors are prevalent in politics and have been established as major linguistic devices. Therefore, many political figures extensively employ metaphors. The research recommends exploring other types of metaphors in different genres.